Analysis of Business Ethics on Micro, Small, and Medium Enterprises (MSMEs) Bubur Ayam Mang Jay Telang, Bangkalan - Zaenab; Abdur Rohman (Managing: Jurnal Bisnis dan Manajemen, 2025)
ABSTRACK This research aims to analyze the application of business ethics in the operations of the Mang Jay Chicken Bubur MSME. This research uses interview and observation methods to collect data regarding the business ethics practices implemented. The research results show that Bubur Ayam Mang Jay applies the principles of business ethics such as honesty, integrity, fairness, responsibility and transparency in every aspect of its operations. The application of business ethics has a positive impact on business reputation and performance, increasing customer loyalty and employee productivity. Based on these findings, it is recommended that other MSMEs adopt similar practices and conduct ongoing training on business ethics for employees. Future research is recommended to conduct comparative studies in various sectors and combine qualitative and quantitative approaches to gain a more comprehensive understanding.